Interference-based topology control algorithm for noise removal and delay-constrained mobile ad hoc networks using clustering technology - Kiruthika, S; Iswarya, N; Sartiha, A; Kalaivani, K; Ulaga Priya, K (International Journal of Engineering and Technology, 2018)
MANET is ad hoc network which is in the top layer of the network. This ad hoc network are connected by mobile devices with flexible topology network to control the delay constrain in the mobile ad hoc network for noise removal in network. The transmission power is managed to minimize the interference taking into account the topology control algorithm also accounts the delay constraint and finds the duplicate data.Â Â